LCD Panel

The liquid crystal panel with a conductive layer and anti-reflection film addresses display defects from static electricity, enhancing visibility and safety in environments with electronic devices by reducing light reflectance and static discharge effects.

CN114761865BActive Publication Date: 2024-12-20NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080080315.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-10-07
Publication Date
2024-12-20
Estimated Expiration
2040-10-07

AI Technical Summary

Technical Problem

Liquid crystal display devices without an ITO layer on the polarizing film side face challenges in preventing display defects caused by static electricity, especially in environments with other electronic devices, and require improved visibility and safety, particularly in vehicle-mounted displays.

Method used

A liquid crystal panel design featuring a polarizing film with an anti-reflection film and a conductive layer, where the conductive layer has a surface resistivity of 1.0×10^6 Ω/□ or less, directly or indirectly contacting the liquid crystal unit, and is positioned between the anti-reflection film and the adhesive layer, reducing light reflectance to less than 1.1% to enhance visibility and prevent display defects.

Benefits of technology

The design improves visibility and prevents display defects in liquid crystal display devices by effectively dissipating static electricity, ensuring clear and safe operation even in environments prone to static discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114761865B_ABST
    Figure CN114761865B_ABST
Patent Text Reader

Abstract

The present invention provides a liquid crystal panel that can improve the visual recognition of a liquid crystal display device while preventing display defects caused by charging of the liquid crystal display device. The liquid crystal panel of the present invention comprises a polarizing film (15) with an anti-reflection film and a liquid crystal unit (25), wherein the polarizing film (15) with an anti-reflection film has an anti-reflection film (10), a polarizing film (20) and an adhesive layer (30) in the stacking direction, and also has a conductive layer (40). No conductive layer is provided between the polarizing film with an anti-reflection film and the liquid crystal unit. The surface resistivity of the conductive layer of the polarizing film with an anti-reflection film is 1.0×10 6 Ω / □ or less. When the polarizing film with an antireflection film is laminated with the alkali-free glass in a manner that the adhesive layer is directly in contact with the alkali-free glass, when light from the CIE standard light source D65 is incident from the surface opposite to the adhesive layer, reflected light with a light reflectance Y of 1.1% or less is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal panel. Background Art

[0002] The liquid crystal display device includes, for example, a liquid crystal panel having a polarizing film disposed on a visible side of a liquid crystal cell and an illumination system for irradiating light to the liquid crystal panel. The liquid crystal display device displays an image by applying voltage to the liquid crystal cell and adjusting the alignment of liquid crystal molecules contained in the liquid crystal cell.

[0003] For a liquid crystal display device, static electricity is generated during manufacturing, for example, when a polarizing film is attached to a liquid crystal cell via an adhesive layer, or during use, for example, when a user touches the liquid crystal display device. The liquid crystal display device may be charged due to the static electricity. If the liquid crystal display device is charged, the orientation of the liquid crystal molecules contained in the liquid crystal cell is disordered, and poor display may occur. In order to prevent poor display caused by charging of the liquid crystal display device, it is known that an ITO (indium tin oxide) layer is arranged on the surface of the liquid crystal cell on the side of the polarizing film, for example.

[0004] However, the ITO layer is sometimes omitted from the perspective of cost, etc. For example, Patent Documents 1 and 2 disclose a liquid crystal panel in which an ITO layer is not disposed on the surface of a liquid crystal cell on the polarizing film side, and a polarizing film with an adhesive layer is directly in contact with the liquid crystal cell.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2018 / 181477

[0008] Patent Document 2: Japanese Patent No. 5679337 Summary of the invention

[0009] Problems to be solved by the invention

[0010] When a liquid crystal display device without an ITO layer on the surface of the liquid crystal cell on the polarizing film side is used in an environment where static electricity is particularly likely to be generated, such as in an environment where other electronic devices are present around, such as the interior of a vehicle, it is difficult to fully prevent display defects caused by charging. In addition, when a liquid crystal display device is used as a vehicle-mounted display, for example, good visual recognition is required from the perspective of safety.

[0011] Therefore, an object of the present invention is to provide a liquid crystal panel that can improve the visibility of a liquid crystal display device while preventing display defects caused by charging of the liquid crystal display device.

[0012] Solutions to the problem

[0013] The present invention provides a liquid crystal panel, which comprises a polarizing film with an anti-reflection film and a liquid crystal unit, wherein the polarizing film with an anti-reflection film has an anti-reflection film, a polarizing film and an adhesive layer in the stacking direction, and further has a conductive layer.

[0014] No conductive layer is provided between the polarizing film with antireflection film and the liquid crystal unit.

[0015] The surface resistivity of the conductive layer of the polarizing film with an antireflection film is 1.0×10 6 Ω / □ or less,

[0016] When the above-mentioned polarizing film with anti-reflection film is stacked together with the above-mentioned alkali-free glass in a manner that the above-mentioned adhesive layer is directly in contact with the above-mentioned alkali-free glass, when light from the CIE standard light source D65 is incident from the surface on the opposite side of the above-mentioned adhesive layer, reflected light with a light reflectance Y of less than 1.1% is generated.

[0017] Effects of the Invention

[0018] According to the present invention, a liquid crystal panel capable of improving the visibility of a liquid crystal display device while preventing display defects caused by charging of the liquid crystal display device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a cross-sectional view of a liquid crystal panel according to one embodiment of the present invention.

[0020] Figure 2 This is a cross-sectional view showing an example of an antireflection film.

[0021] Figure 3 It is a cross-sectional view showing another example of the antireflection film.

[0022] Figure 4 It is a cross-sectional view showing a modified example of a liquid crystal panel.

[0023] Figure 5 This is a cross-sectional view showing another modified example of the liquid crystal panel.

[0024] Figure 6 FIG. 1 is a graph showing the reflected light from the polarizing film with an antireflection film in the embodiment and the comparative example. * Value and b * A graph of the relationship of the values. DETAILED DESCRIPTION

[0025] Hereinafter, the present invention will be described in detail, but the following description is not intended to limit the present invention to specific embodiments.

[0026] (Embodiment of Liquid Crystal Panel)

[0027] like Figure 1 As shown, the liquid crystal panel 100 of the present embodiment includes a polarizing film 15 with an anti-reflection film and a liquid crystal unit 25. No conductive layer, such as an ITO layer, is provided between the polarizing film 15 with an anti-reflection film and the liquid crystal unit 25, and the polarizing film 15 with an anti-reflection film is directly or indirectly in contact with the liquid crystal unit 25. Other layers other than the conductive layer may be arranged between the polarizing film 15 with an anti-reflection film and the liquid crystal unit 25 within the scope that does not hinder the effect of the present invention. The polarizing film 15 with an anti-reflection film has an anti-reflection film 10, a polarizing film 20 and an adhesive layer 30 in sequence in the stacking direction, and also has a conductive layer 40. The conductive layer 40 is, for example, arranged between the polarizing film 20 and the adhesive layer 30, and is in contact with the polarizing film 20 and the adhesive layer 30, respectively. When the conductive layer 40 is arranged between the polarizing film 20 and the adhesive layer 30, there is a tendency that the degradation of the conductive layer 40 is suppressed. However, the conductive layer 40 may be disposed at a position other than between the polarizing film 20 and the pressure-sensitive adhesive layer 30 , for example, between the anti-reflection film 10 and the polarizing film 20 .

[0028] In the polarizing film with an antireflection film 15, the surface resistivity of the conductive layer 40 is 1.0×10 6 Ω / □ or less. The conductive layer 40 having a surface resistivity as low as this can prevent display defects caused by charging of the liquid crystal display device having the liquid crystal panel 100 even in an environment where static electricity is easily generated. The surface resistivity of the conductive layer 40 can be determined by the following method. First, a laminate in which the surface of the conductive layer 40 is exposed to the outside is prepared. As such a laminate, for example, there can be mentioned: a laminate L including a polarizing film 20 and a conductive layer 40. Next, the surface resistivity of the surface of the conductive layer 40 in the prepared laminate is measured. The surface resistivity can be measured according to the method specified in JIS K7194:1994 or JIS K6911:1995. As an example, when the surface resistivity of the conductive layer 40 is less than 1.0×10 5 Ω / □, the surface resistivity of the conductive layer 40 can be measured using Loresta-GP MCP-T600 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with the method specified in JIS K7194:1994. 5When the surface resistivity of the conductive layer 40 is 0.0447 W / m3 or more, the surface resistivity of the conductive layer 40 can be measured using Hiresta-UP MCP-HT450 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) according to the method specified in JIS K6911: 1995. The measured value obtained by the above measurement can be regarded as the surface resistivity of the conductive layer 40 in the polarizing film 15 with an antireflection film.

[0029] The surface resistivity of the conductive layer 40 is preferably 5.0×10 5 Ω / □ or less, more preferably 1.0×10 5 Ω / □ or less, more preferably 1.0×10 4 Ω / □ or less, particularly preferably 1.0×10 3 Ω / □ or less. The lower limit of the surface resistivity of the conductive layer 40 is not particularly limited, but is, for example, 1.0×10 2 Ω / □. When the liquid crystal panel 100 is used in a liquid crystal display device having a touch sensor or a touch panel, the surface resistivity of the conductive layer 40 may be greater than 5.0×10 2 Ω / □.

[0030] When the polarizing film 15 with an anti-reflection film is laminated with the alkali-free glass in a manner that the adhesive layer 30 is directly in contact with the alkali-free glass, light from the CIE standard light source D65 is incident from the surface opposite to the adhesive layer 30 (typically the surface of the anti-reflection film 10), reflected light with a light reflectance Y of less than 1.1% is generated. By generating such reflected light, the polarizing film 15 with an anti-reflection film can suppress the reflection of light in the liquid crystal panel 100, thereby improving the visual recognition of the liquid crystal display device. It should be noted that the light reflectance Y refers to the Y value of the three stimulus values ​​(X, Y and Z) in the XYZ color system (CIE1931). The three stimulus values ​​are specified in detail in JIS Z8701:1999.

[0031] In detail, the above-mentioned light reflectance Y can be specified by the following method. First, the polarizing film 15 with an anti-reflection film is adhered to the alkali-free glass using the adhesive layer 30. Alkali-free glass is a glass that does not substantially contain alkali components (alkali metal oxides). Specifically, the weight ratio of the alkali components in the glass is, for example, less than 1000 ppm, and further less than 500 ppm. The alkali-free glass is, for example, in the form of a plate and has a thickness of more than 0.5 mm. Next, a black film is adhered to the surface of the alkali-free glass on the opposite side of the surface adhered to the polarizing film 15 with an anti-reflection film. Next, light from the CIE standard light source D65 is incident on the surface of the polarizing film 15 with an anti-reflection film on the side of the anti-reflection film 10 at an incident angle of 5°. The spectral reflectance within the wavelength range of 360nm to 740nm of the mirror reflected light generated at this time can be specified, and the light reflectance Y in the XYZ color system (CIE1931) can be specified based on the spectral reflectance.

[0032] The light reflectance Y is preferably 1.0% or less, more preferably 0.9% or less, further preferably 0.8% or less, and particularly preferably 0.7% or less. The lower limit of the light reflectance Y is not particularly limited, and is, for example, 0.1%.

[0033] The above reflected light is at L * a * b * a in the color system (CIE1976) * Value and b * The value is not particularly limited, but preferably satisfies the following relational expressions (1) and (2).

[0034] -10≤a * ≤10 (1)

[0035] -18≤b * ≤5 (2)

[0036] The above a * Value and b * The value can be specified by the following formulas (i) and (ii) specified in JIS Z8781-4:2013 using tristimulus values ​​(X, Y, and Z) of reflected light in an XYZ color system.

[0037] [Mathematical formula 1]

[0038] a * =500[f(X / X n )-f(Y / Y n )] (i)

[0039] b * =200[f(Y / Y n )-f(Z / Z n (ii)

[0040] The above a * The value is preferably -6 or more and 6 or less, and more preferably -3 or more and 3 or less. * The value is preferably -15 to 3, more preferably -10 to 2, further preferably -6 to 2, and particularly preferably -5 to 2. * Value and b * The values ​​may also satisfy the following relations (3) and (4).

[0041] b * ≥-1.5a * -15 (3)

[0042] b * ≤-1.5a * +7.5 (4)

[0043] In addition, a * Value and b * The values ​​may also satisfy the following equations (5) and (6).

[0044] b * ≥-1.5a * -5 (5)

[0045] b * ≤-1.5a * +4.5 (6)

[0046] The L of the reflected light * The value is, for example, 12 or less, preferably 10 or less, more preferably 8 or less, and further preferably 7 or less. * The lower limit of the value is not particularly limited, and is, for example, 3. * The value can be specified according to the following formula (iii) specified in JIS Z 8781-4: 2013 using the above-mentioned tristimulus values.

[0047] [Mathematical formula 2]

[0048] L * =116f(Y / Y n )-16 (iii)

[0049] Meet L * Value = 0, a * Value = 0 and b * The color difference ΔE between the light having a color value of 0 (light having a completely natural hue) and the above-mentioned reflected light is, for example, 22 or less, preferably 18 or less, more preferably 15 or less, further preferably 10 or less, and particularly preferably 8 or less. The lower limit of the color difference ΔE is not particularly limited, and is, for example, 3. The color difference ΔE can be calculated using the L value of the reflected light.* Value, a * Value and b * The value was calculated based on the following formula (iv).

[0050] AE * ={(L * ) 2 +(a * ) 2 +(b * ) 2} 1 / 2 (iv)

[0051] [Anti-reflective film]

[0052] like Figure 2 As shown, the antireflection film 10 has, in order in the stacking direction, a first high refractive index layer 1, a first low refractive index layer 2, a second high refractive index layer 3, and a second low refractive index layer 4. The first high refractive index layer 1 is, for example, in contact with the polarizing film 20. The second low refractive index layer 4 is, for example, located closest to the visible side among these layers.

[0053] The high refractive index layers 1 and 3 are layers having a refractive index higher than that of the low refractive index layers 2 and 4, and their refractive indexes are, for example, in the range of 1.6 to 3.2. The refractive index of the first high refractive index layer 1 may be the same as or different from that of the second high refractive index layer 3. In this specification, unless otherwise specified, "refractive index" refers to a value measured at a temperature of 25°C using light of a wavelength λ=550nm and in accordance with the provisions of JIS K0062:1992.

[0054] In a preferred embodiment of the present invention, the high refractive index layers 1 and 3, for example, contain a binder resin and inorganic particles dispersed in the binder resin. The binder resin is typically a cured product of an ionizing radiation-curable resin, more specifically, a cured product of an ultraviolet-curable resin. As ultraviolet-curable resins, there can be cited resins containing polymers or oligomers having substituents capable of free radical polymerization, such as (meth)acrylate resins. (Meth)acrylate resins as ultraviolet-curable resins include polymers or oligomers such as epoxy (meth)acrylate, polyester (meth)acrylate, acrylic (meth)acrylate, and ether (meth)acrylate. In addition to the above-mentioned polymers or oligomers, the (meth)acrylate resin may further contain a free radical polymerizable monomer (precursor). The molecular weight of the monomer is, for example, 200 to 700. Specific examples of the monomer include pentaerythritol triacrylate (PETA: molecular weight 298), neopentyl glycol diacrylate (NPGDA: molecular weight 212), dipentaerythritol hexaacrylate (DPHA: molecular weight 632), dipentaerythritol pentaacrylate (DPPA: molecular weight 578), and trimethylolpropane triacrylate (TMPTA: molecular weight 296). As required, the ionizing radiation curable resin may also contain an initiator. Examples of the initiator include: UV free radical generators (IRGACURE 907, IRGACURE 127, IRGACURE 192, etc. manufactured by Ciba Specialty Chemicals Co.), and benzoyl peroxide. The above-mentioned binder resin may include other resins in addition to the cured product of the ionizing radiation curable resin. The other resins may be thermosetting resins or thermoplastic resins. Examples of other resins include aliphatic resins (e.g., polyolefins), urethane resins, and the like.

[0055] The refractive index of the binder resin is, for example, 1.40 to 1.60. The amount of the binder resin blended is, for example, 10 to 80 parts by weight, or preferably 20 to 70 parts by weight, based on 100 parts by weight of the high refractive index layer to be formed.

[0056] The material of the inorganic fine particles is, for example, a metal oxide. Specific examples of metal oxides include zirconium oxide (refractive index: 2.19), aluminum oxide (refractive index: 1.56 to 2.62), titanium oxide (refractive index: 2.49 to 2.74), and silicon oxide (refractive index: 1.25 to 1.46). These metal oxides not only have low light absorption, but also have a higher refractive index than organic materials such as ionizing radiation curable resins and thermoplastic resins, and are therefore suitable for adjusting the refractive index of the high refractive index layers 1 and 3. The inorganic fine particles preferably contain zirconium oxide or titanium oxide.

[0057] The refractive index of the inorganic fine particles is, for example, 1.60 or more, preferably 1.70 to 2.80, and more preferably 2.00 to 2.80. Inorganic fine particles having a refractive index of 1.60 or more are suitable for adjusting the refractive index of the high refractive index layers 1 and 3. The average particle size of the inorganic fine particles is, for example, 1 nm to 100 nm, preferably 10 nm to 80 nm, and more preferably 20 nm to 70 nm. The average particle size of the inorganic fine particles refers to the particle size (d50) equivalent to 50% of the volume accumulation in the particle size distribution measured by, for example, a laser diffraction particle size analyzer.

[0058] The inorganic particles may not be surface-modified, but are preferably surface-modified. The surface-modified inorganic particles tend to be well dispersed in the binder resin. The surface modification is performed, for example, by coating a surface modifier on the surface of the inorganic particles to form a surface modifier layer. Examples of the surface modifier include coupling agents such as silane coupling agents and titanate coupling agents; and surfactants such as fatty acid surfactants. If such a surface modifier is used, the wettability of the binder resin and the inorganic particles is improved, and there is a tendency for the interface between the binder resin and the inorganic particles to be stabilized.

[0059] The amount of inorganic particles is, for example, 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, relative to 100 parts by weight of the high refractive index layer formed. When the amount of inorganic particles is within the above range, the antireflection film has sufficient mechanical properties and tends to be able to sufficiently reduce the light reflectance ratio Y of the reflected light.

[0060] The refractive index of the high refractive index layers 1 and 3 including the binder resin and the inorganic fine particles is, for example, 1.6 to 2.6, or preferably 1.7 to 2.2.

[0061] In another preferred embodiment of the present invention, the high refractive index layers 1 and 3 contain metal oxides or metal nitrides, and are preferably substantially formed of metal oxides or metal nitrides. Specific examples of metal oxides include titanium oxide (TiO2), indium / tin oxide (ITO), niobium oxide (Nb2O5), yttrium oxide (Y2O3), indium oxide (In2O3), tin oxide (SnO2), zirconium oxide (ZrO2), hafnium oxide (HfO2), antimony oxide (Sb2O3), tantalum oxide (Ta2O5), zinc oxide (ZnO), and tungsten oxide (WO3). As a specific example of metal nitrides, silicon nitride (Si3N4) can be cited. The high refractive index layers 1 and 3 preferably contain niobium oxide (Nb2O5) or titanium oxide (TiO2). The refractive index of the high refractive index layer composed of metal oxides or metal nitrides is, for example, 2.00 to 2.60, preferably 2.10 to 2.45.

[0062] The material of the first high refractive index layer 1 may be the same as or different from that of the second high refractive index layer 3 .

[0063] The physical film thickness of the first high refractive index layer 1 is, for example, 9 nm to 15 nm, preferably 11 nm to 13 nm. The optical film thickness of the first high refractive index layer 1 is, for example, 20 nm to 35 nm, preferably 25 nm to 30 nm. It should be noted that in this specification, the optical film thickness is a value represented by the product of the refractive index of light with a wavelength of 550 nm and the physical film thickness.

[0064] The physical film thickness of the second high refractive index layer 3 is, for example, 98 nm to 124 nm, or preferably 111 nm to 120 nm. The optical film thickness of the second high refractive index layer 3 is, for example, 230 nm to 290 nm, or preferably 260 nm to 280 nm.

[0065] The low refractive index layers 2 and 4 are layers having a refractive index lower than that of the high refractive index layers 1 and 3, and their refractive indexes are, for example, 1.35 to 1.55, preferably 1.40 to 1.50. By appropriately adjusting the difference in refractive index between the low refractive index layers 2 and 4 and the high refractive index layers 1 and 3, there is a tendency to suppress the reflection of light. The refractive index of the first low refractive index layer 2 may be the same as or different from that of the second low refractive index layer 4.

[0066] As the material of low refractive index layer 2 and 4, for example, metal oxide and metal fluoride can be enumerated. As the specific example of metal oxide, silicon oxide (SiO2) can be enumerated. As the specific example of metal fluoride, magnesium fluoride and fluorinated silicic acid can be enumerated. From the viewpoint of refractive index, the material of low refractive index layer 2 and 4 is preferably magnesium fluoride and fluorinated silicic acid, and from the viewpoints such as manufacturing ease, mechanical strength, moisture resistance, silicon oxide is preferred. If various characteristics are considered comprehensively, silicon oxide is preferred. The material of the first low refractive index layer 2 can be the same as or different from the second low refractive index layer 4.

[0067] The material of the low refractive index layer 2 and 4 can be a cured product of a curable fluorine-containing resin. The curable fluorine-containing resin, for example, has a structural unit from a fluorine-containing monomer and a structural unit from a cross-linking monomer. As specific examples of fluorine-containing monomers, for example, there can be mentioned: fluoroolefins (vinyl fluoride, vinylidene fluoride, tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoro-2,2-dimethyl-1,3-dioxole, etc.), (meth)acrylate derivatives with partially or completely fluorinated alkyl groups (Viscoat 6FM (manufactured by Osaka Organic Chemical Co., Ltd.), M-2020 (manufactured by Daikin Co., Ltd.), etc.), and completely or partially fluorinated vinyl ethers. As cross-linking monomers, for example, there can be mentioned: (meth)acrylate monomers having cross-linking functional groups in the molecule such as glycidyl methacrylate; (meth)acrylate monomers having functional groups such as carboxyl, hydroxyl, amino, and sulfonic acid groups ((meth)acrylic acid, hydroxymethyl (meth)acrylate, (meth)acrylate hydroxyalkyl ester, (meth)acrylate allyl ester, etc.). The fluorine-containing resin may have a structural unit derived from other monomers (for example, an olefin monomer, a (meth)acrylate monomer, or a styrene monomer) other than the above-mentioned compounds.

[0068] The physical film thickness of the first low refractive index layer 2 is, for example, 26 nm to 34 nm, or preferably 27 nm to 31 nm. The optical film thickness of the first low refractive index layer 2 is, for example, 38 nm to 50 nm, or preferably 40 nm to 45 nm.

[0069] The physical film thickness of the second low refractive index layer 4 is, for example, 68 nm to 88 nm, or preferably 72 nm to 79 nm. The optical film thickness of the second low refractive index layer 4 is, for example, 100 nm to 128 nm, or preferably 105 nm to 115 nm.

[0070] The method for making the high refractive index layer and the low refractive index layer is not particularly limited. When these layers contain resins, these layers can be formed by a so-called wet process (curing after applying the resin composition). When these layers are composed of metal oxides, metal fluorides, metal nitrides, etc., these layers can be formed by a so-called dry process. As specific examples of dry processes, PVD (physical vapor deposition, Physical Vapor Deposition) method and CVD (chemical vapor deposition, Chemical Vapor Deposition) method can be cited. As a PVD method, for example, vacuum evaporation method, reactive evaporation method, ion beam assisted method, sputtering method, ion plating method can be cited. As a CVD method, for example, a plasma CVD method can be cited. From the viewpoint of reducing the deviation of the hue of the reflected light, as a dry process, sputtering method is preferred.

[0071] Figure 2The antireflection film 10 may further include other components besides the high refractive index layer and the low refractive index layer. Figure 3 Another example of the antireflection film is shown. Figure 3 The antireflection film 11 further includes a substrate 5 and an adhesive layer 6. The substrate 5 is, for example, disposed between the first high refractive index layer 1 and the polarizing film 20 and in contact with the first high refractive index layer 1. The adhesive layer 6 is, for example, disposed between the substrate 5 and the polarizing film 20 and in contact with the substrate 5 and the polarizing film 20, respectively.

[0072] The substrate 5 includes, for example, a transparent resin film. Examples of the material of such a resin film include cellulose resins (cellulose triacetate, cellulose diacetate, cellulose propionate, cellulose butyrate, cellulose acetate propionate, nitrocellulose, etc.), polyamide resins (nylon-6, nylon-66, etc.), polyimide resins, polycarbonate resins, polyester resins (polyethylene terephthalate, polyethylene naphthalate, polyethylene 1,4-cyclohexanedimethanol terephthalate, polyethylene-1,2-diphenoxyethane-4,4'-dicarboxylate, polybutylene terephthalate, etc.), polyolefin resins (polyethylene, polypropylene, polymethylpentene, etc.), polysulfone resins, polyethersulfone resins, polyarylate resins, polyetherimide resins, polymethyl methacrylate resins, polyetherketone resins, polystyrene resins, polyvinyl chloride resins, polyvinyl alcohol resins, ethylene vinyl alcohol resins, (meth)acrylic resins, (meth)acrylonitrile resins, etc. The substrate 5 may be a single resin film layer, a laminate of multiple resin films, or a laminate of a resin film and a hard coating layer described later. The substrate 5 may contain additives. Specific examples of additives include antistatic agents, ultraviolet absorbers, plasticizers, lubricants, colorants, antioxidants, flame retardants, and the like.

[0073] In a preferred embodiment of the present invention, the substrate 5 is a triacetyl cellulose (TAC) film. The triacetyl cellulose film can also function as a protective film for the polarizer. Therefore, by using the anti-reflection film 11 having the substrate 5 formed of the triacetyl cellulose film, the transparent protective film of the polarizing film 20 on the visible side can sometimes be omitted.

[0074] In another preferred embodiment of the present invention, the substrate 5 includes a hard coating layer. The substrate 5 may be composed of a hard coating layer, or may be a laminate of a resin film and a hard coating layer. The hard coating layer is, for example, a cured layer of an ionizing radiation curable resin. As ionizing radiation, for example, ultraviolet rays, visible light, infrared rays, electron beams, preferably ultraviolet rays. That is, the ionizing radiation curable resin is preferably an ultraviolet curable resin. As ultraviolet curable resins, for example, (meth) acrylic resins, silicone resins, polyester resins, carbamate resins, amide resins, epoxy resins, etc. may be mentioned. As (meth) acrylic resins, for example, a cured product (polymer) formed by ultraviolet curing of a multifunctional monomer containing a (meth) acryloyloxy group. For example, one multifunctional monomer may be used or two or more may be used in combination. For example, the multifunctional monomer may be mixed with a photopolymerization initiator.

[0075] Inorganic particles or organic particles may be dispersed in the hard coating layer. The average particle size (d50) of the particles is, for example, 0.01 μm to 3 μm. As particles dispersed in the hard coating layer, silicon oxide (SiO2) is preferred from the viewpoints of refractive index, stability, heat resistance, etc. The hard coating layer may contain additives. Specific examples of additives include leveling agents, fillers, dispersants, plasticizers, ultraviolet absorbers, surfactants, antioxidants, and thixotropic agents. In addition, a concavo-convex shape may be formed on the surface of the hard coating layer. The hard coating layer having a concavo-convex shape on the surface has a light diffusion function (anti-glare).

[0076] The physical film thickness of the substrate 5 is not particularly limited. When the substrate 5 is a single resin film layer or a laminate of multiple resin films, the physical film thickness of the substrate 5 is, for example, in the range of 10 μm to 200 μm. When the substrate 5 includes a hard coating layer, the physical film thickness of the hard coating layer is, for example, in the range of 1 μm to 50 μm.

[0077] The refractive index of the substrate 5 (when the substrate 5 has a laminated structure, the refractive index of the layer closest to the first high refractive index layer 1 ) is, for example, 1.3 to 1.8, or preferably 1.4 to 1.7.

[0078] The adhesive layer 6 is a layer containing an adhesive. As the adhesive contained in the adhesive layer 6, for example, a resin having adhesiveness can be cited. Examples of such resins include acrylic resins, acrylic urethane resins, urethane resins, silicone resins, etc. The adhesive layer 6 preferably contains an acrylic adhesive composed of an acrylic resin.

[0079] The adhesive layer 6 may further contain additives as required. Examples of the additives include crosslinking agents, tackifiers, plasticizers, pigments, dyes, fillers, anti-aging agents, conductive materials, ultraviolet absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, and the like. Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, peroxide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc.

[0080] The physical film thickness of the adhesive layer 6 is, for example, 5 μm to 100 μm, or preferably 10 μm to 50 μm.

[0081] The anti-reflection film 11 may further include other components besides the substrate 5 and the adhesive layer 6. For example, the anti-reflection film 11 may further include an anti-glare layer disposed between the substrate 5 and the first high refractive index layer 1. The anti-reflection film 11 may further include an adhesion layer disposed between specific components (for example, between the substrate 5 and the first high refractive index layer 1, or between the anti-glare layer and the first high refractive index layer 1). The adhesion layer is a layer that improves the adhesion between components, and for example, contains silicon, SiO x (x<2) The physical film thickness of the adhesion layer is, for example, 1 nm to 10 nm, preferably 2 nm to 5 nm. The refractive index of the adhesion layer is, for example, 1 to 2.5.

[0082] The anti-reflection films 10 and 11 may further include an antifouling layer disposed closer to the visible side than the second low refractive index layer 4 and in contact with the second low refractive index layer 4. The antifouling layer is a layer having an antifouling effect, and for example, contains at least one selected from fluorine resins and silicone resins. The physical film thickness of the antifouling layer is, for example, 5 nm to 13 nm, preferably 5 nm to 10 nm. The refractive index of the antifouling layer is, for example, 1 to 2.

[0083] When light from CIE standard light source D65 is incident on the anti-reflection films 10 and 11, the reflected light is preferably * a * b * a1 in the color system * Value and b1 * The absolute value of a1 is small. * The value is, for example, -6 to 6, more preferably -3 to 3. b1 * The value is, for example, -15 to 3, preferably -10 to 2, and more preferably -5 to 2. a1 * Value and b1 *The value can be specified by the following method. First, the first high refractive index layer 1, the first low refractive index layer 2, the second high refractive index layer 3 and the second low refractive index layer 4 of the anti-reflection film 10 are sequentially stacked on the black film, or the anti-reflection film 11 is adhered to the black film through the adhesive layer 6 of the anti-reflection film 11. Next, light from the CIE standard light source D65 is incident on the surface of the anti-reflection film 10 or 11 on the second low refractive index layer side at an incident angle of 5°. The spectral reflectance in the range of 360nm to 740nm of the specific wavelength of the mirror reflected light generated at this time is determined, and the tristimulus values ​​in the XYZ color system are determined based on the spectral reflectance. Using the obtained tristimulus values, a1 is specified by the above formulas (i) and (ii). * Value and b1 * value.

[0084] The light reflectance Y1 of the reflected light is, for example, 0.3% or less, or preferably 0.2% or less.

[0085] [Polarizing film]

[0086] The polarizing film 20 is a laminate including a polarizer and a transparent protective film. The transparent protective film is arranged, for example, in contact with the main surface (the surface with the largest area) of the layered polarizer. The polarizer can be arranged between two transparent protective films. There is no particular limitation on the polarizer, and examples thereof include polarizers obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and uniaxially stretching them; polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. The polarizer is preferably formed of dichroic substances such as polyvinyl alcohol films and iodine.

[0087] The thickness of the polarizer is not particularly limited, and is, for example, 80 μm or less. The thickness of the polarizer may be 10 μm or less, preferably 1 to 7 μm. Such a thin polarizer has less uneven thickness and excellent visual recognition. The dimensional change of the thin polarizer is suppressed, and the durability is excellent. By using a thin polarizer, the polarizing film 20 can be thinned.

[0088] As the material of the transparent protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the transparent protective film can be a thermosetting resin or an ultraviolet curing resin such as (meth)acrylic, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film 20 has two transparent protective films, the materials of the two transparent protective films can be the same or different. For example, a transparent protective film made of a thermoplastic resin can be bonded to one main surface of the polarizer using an adhesive, and a transparent protective film made of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The transparent protective film may contain one or more optional additives.

[0089] The transparent protective film may have optical properties such as anti-glare properties and anti-reflection properties. The transparent protective film may be a film that functions as a phase difference film. In this specification, a phase difference film refers to a film having birefringence in the in-plane direction or the thickness direction. Films that function as phase difference films include, for example, films obtained by stretching a polymer film, films obtained by orienting and fixing a liquid crystal material, and the like.

[0090] The adhesive used to bond the polarizer to the transparent protective film is not particularly limited as long as it is optically transparent, and examples thereof include aqueous, solvent-based, hot melt-based, radical-curable, and cation-curable adhesives, with aqueous adhesives and radical-curable adhesives being preferred.

[0091] The thickness of the polarizing film 20 is, for example, 10 μm to 500 μm. The total light transmittance of the polarizing film 20 is not particularly limited, and is, for example, 30% to 50%. In this specification, "total light transmittance" refers to the transmittance of light in the wavelength range of 380 nm to 700 nm. The total light transmittance can be measured based on the provisions of JIS K7361-1:1997. The total light transmittance is measured using CIE standard light source D65.

[0092] When the polarizing film 20 is incident with light from the CIE standard light source D65, the a value of the transmitted light in the Hunter Lab color system is preferably -6.0 to 0, more preferably -3.0 to -0.5, and particularly preferably -1.8 to -1.2. The b value of the above-mentioned transmitted light in the Hunter Lab color system is preferably 1.0 to 10, more preferably 1.5 to 5.0, and particularly preferably 2.2 to 4.0. The a value and b value of the transmitted light in the Hunter Lab color system can be specified by the following method. First, the transmittance of the light from the CIE standard light source D65 in the polarizing film 20 is measured using an integrating sphere of a spectrophotometer. For the obtained transmittance, the visibility correction (780 to 380 nm: 5 nm interval) is performed using the 2-degree field of view XYZ system specified in JIS Z8701:1999, thereby specifying the a value and b value of the transmitted light in the Hunter Lab color system.

[0093] [Conductive layer of polarizing film with anti-reflection film]

[0094] The conductive layer 40 is a layer containing a conductive material. The conductive material may also be a material other than ITO, such as a conductive polymer, a composite of a conductive polymer and a dopant, an ionic surfactant, conductive particles, an ionic compound, etc. From the perspective of transparency, total light transmittance, appearance, antistatic effect, and stability of the antistatic effect in a high temperature or humid environment, it is preferred that the conductive layer 40 contains a conductive polymer. In the case where the conductive layer 40 contains a conductive polymer as a conductive material, compared with the case where the conductive particles are contained, even if the thickness of the conductive layer 40 is adjusted relatively greatly, it is not easy to generate fog. Therefore, even if the conductive layer 40 is configured between the liquid crystal unit 25 and the polarizer, the conductive layer 40 containing the conductive polymer is not easy to eliminate polarized light, and it is not easy to reduce the contrast of the image displayed by the liquid crystal display device. In the case where the conductive layer 40 contains a conductive polymer as a conductive material, there is a tendency that the refractive index of the conductive layer 40 is low compared with the case where the conductive particles are contained. Therefore, the conductive layer 40 containing a conductive polymer is suitable for further reducing the reflectivity of light of the liquid crystal panel 100.

[0095] As the conductive polymer, for example, there can be mentioned: polythiophene, polyaniline, polypyrrole, polyquinoxaline, polyacetylene, polyphenylene vinylene, polynaphthalene and their derivatives. The conductive material may contain one or more of these conductive polymers. As the conductive polymer, polythiophene, polyaniline and their derivatives are preferred, and polythiophene derivatives are particularly preferred. Polythiophene, polyaniline and their derivatives function, for example, as water-soluble or water-dispersible conductive polymers. In the case where the conductive polymer is water-soluble or water-dispersible, the conductive layer 40 can be made using an aqueous solution or an aqueous dispersion of the conductive polymer. In this case, the production of the conductive layer 40 does not require the use of a non-aqueous organic solvent, and therefore, the corrosion of the polarizing film 20 and the like caused by the organic solvent can be suppressed.

[0096] The conductive polymer may have a hydrophilic functional group. Examples of the hydrophilic functional group include a sulfonic group, an amino group, an amide group, an imino group, a hydroxyl group, a thiol group, a hydrazine group, a carboxyl group, a sulfate group, a phosphate group, and salts thereof (e.g., a quaternary ammonium salt group). When the conductive polymer has a hydrophilic functional group, there is a tendency that the conductive polymer is easily soluble in water, or that the conductive polymer in a microparticle form is easily dispersed in water.

[0097] From the viewpoint of conductivity and chemical stability, the conductive polymer is preferably poly(3,4-disubstituted thiophene). Examples of poly(3,4-disubstituted thiophene) include poly(3,4-alkylenedioxythiophene) and poly(3,4-dialkoxythiophene), and poly(3,4-alkylenedioxythiophene) is preferred. Poly(3,4-alkylenedioxythiophene) has a structural unit represented by the following formula (I), for example.

[0098] [Chemical formula 1]

[0099]

[0100] In formula (I), R 1 For example, it is an alkylene group having 1 to 4 carbon atoms. The alkylene group may be linear or branched. Examples of the alkylene group include methylene, 1,2-ethylene, 1,3-propylene, 1,4-butylene, 1-methyl-1,2-ethylene, 1-ethyl-1,2-ethylene, 1-methyl-1,3-propylene, and 2-methyl-1,3-propylene. Methylene, 1,2-ethylene, and 1,3-propylene are preferred, and 1,2-ethylene is more preferred. The conductive polymer is preferably poly(3,4-methylenedioxythiophene) (PEDOT).

[0101] As a dopant, for example, a polyanion can be cited. When the conductive polymer is polythiophene (or its derivatives), the polyanion can form an ion pair with the polythiophene (or its derivatives) to stably disperse the polythiophene (or its derivatives) in water. As a polyanion, there is no particular limitation, and examples thereof include: carboxylic acid polymers such as polyacrylic acid, polymaleic acid, and polymethacrylic acid; sulfonic acid polymers such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid. The polyanion can also be a copolymer of vinyl carboxylic acid or vinyl sulfonic acid and other monomers. As other monomers, for example: (meth) acrylate compounds; aromatic vinyl compounds such as styrene and vinyl naphthalene. The polyanion is particularly preferably polystyrene sulfonic acid (PSS). As a composite of a conductive polymer and a dopant, for example: a composite of poly (3,4-methylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS) can be cited.

[0102] Examples of the ionic surfactant include quaternary ammonium salt type, Cationic surfactants such as salt type and sulfonium salt type; anionic surfactants such as carboxylic acid type, sulfonate type, sulfate type, phosphate type, phosphite type; sulfobetaine type, alkyl betaine type, alkyl imidazole type Zwitterionic surfactants such as betaine type; nonionic surfactants such as polyol derivatives, β-cyclodextrin inclusion complexes, sorbitan fatty acid monoesters, sorbitan fatty acid diesters, polyoxyalkylene derivatives, and amine oxides.

[0103] As conductive particles, for example, metal oxide particles such as tin oxide, antimony oxide, indium oxide, and zinc oxide can be mentioned, preferably tin oxide particles. As materials of tin oxide particles, for example, tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, titanium oxide-cerium oxide-tin oxide complex, titanium oxide-tin oxide complex, etc. can be mentioned. The average particle size of the conductive particles is, for example, 1 to 100 nm, preferably 2 to 50 nm. The average particle size of the conductive particles refers to the particle size (d50) corresponding to 50% of the volume accumulation in the particle size distribution measured by a laser diffraction particle size analyzer, etc.

[0104] As ionic compounds, for example, alkali metal salts and / or organic cation-anion salts can be mentioned. As alkali metal salts, for example, organic salts and inorganic salts of alkali metals can be mentioned. In this specification, organic cation-anion salts refer to organic salts containing organic cations. The anions contained in the organic cation-anion salts can be organic anions or inorganic anions. Organic cation-anion salts are sometimes referred to as ionic liquids or ionic solids.

[0105] Examples of the alkali metal ion contained in the alkali metal salt include lithium ion, sodium ion and potassium ion, and lithium ion is preferred.

[0106] Examples of anions contained in the organic salt of an alkali metal include: CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - 、(CN)2N - and anions represented by the following general formulae (a) to (d).

[0107] (a)(C n F 2n+1 SO2)2N - (where n is an integer from 1 to 10)

[0108] (b)CF2(C m F 2m SO2)2N - (wherein m is an integer from 1 to 10)

[0109] (c) - O3S(CF2) l SO3 - (wherein l is an integer from 1 to 10)

[0110] (d)(C p F 2p+1 SO2)N - (C q F 2q+1 SO2) (wherein p and q are independently integers of 1 to 10)

[0111] The anion contained in the organic salt of the alkali metal preferably contains a fluorine atom. The anion containing a fluorine atom allows the organic salt of the alkali metal to function as an ionic compound having excellent ion dissociation properties.

[0112] Examples of anions contained in the inorganic salt of an alkali metal include: Cl - Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6- 、ClO4 - 、NO3 - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(FSO2)2N - 、CO3 2- wait.

[0113] As the anion contained in the alkali metal salt, (CF3SO2)2N - 、(C2F5SO2)2N - The (perfluoroalkylsulfonyl)imide represented by the above general formula (a) is particularly preferably (CF3SO2)2N - Represents bis(trifluoromethanesulfonyl)imide.

[0114] Examples of the organic salt of the alkali metal include sodium acetate, sodium alginate, sodium lignin sulfonate, sodium toluene sulfonate, LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, KO3S(CF2)3SO3K, LiO3S(CF2)3SO3K, etc., preferably LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N, Li(CF3SO2)3C, more preferably Li(CF3SO2)2N, Li(C2F5SO2)2N, Li(C4F9SO2)2N. The organic salt of the alkali metal is preferably a fluorine-containing imide lithium salt, and particularly preferably a (perfluoroalkylsulfonyl)imide lithium salt.

[0115] Examples of the inorganic salt of an alkali metal include lithium perchlorate and lithium iodide.

[0116] Examples of the organic cation contained in the organic cation-anion salt include pyridine Cation, piperidine Cation, pyrrolidine Cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazole Cation, Tetrahydropyrimidine Cations, dihydropyrimidines Cation, pyrazole Cationic, pyrazoline Cations, tetraalkylammonium cations, trialkylsulfonium cations, tetraalkyl Cations, etc.

[0117] Examples of anions contained in the organic cation-anion salt include: Cl- Br - ,I - 、AlCl4 - 、Al2Cl7 - 、BF4 - PF6 - 、ClO4 - 、NO3 - 、CH3COO - CF3COO - 、CH3SO3 - CF3SO3 - 、(CF3SO2)3C - 、AsF6 - 、SbF6 - 、NbF6 - 、TaF6 - 、(CN)2N - 、C4F9SO3 - 、C3F7COO - 、(CF3SO2)(CF3CO)N - 、(FSO2)2N - , - O3S(CF2)3SO3 - and anions represented by the above general formulae (a) to (d). The anions contained in the organic cation-anion salt preferably contain fluorine atoms. The anions containing fluorine atoms allow the organic cation-anion salt to function as an ionic compound having excellent ion dissociation properties.

[0118] The ionic compound is not limited to the above-mentioned alkali metal salts and organic cation-anion salts, and can also include inorganic salts such as ammonium chloride, aluminum chloride, cupric chloride, ferrous chloride, ferric chloride, and ammonium sulfate. The conductive material may contain one or more of the above-mentioned ionic compounds.

[0119] Conductive materials are not limited to the above materials, and examples thereof include carbon materials such as acetylene black, Ketjen black, natural graphite, and artificial graphite; titanium black; homopolymers of monomers having cationic conductive groups such as quaternary ammonium salts, zwitterionic conductive groups such as betaine compounds, anionic conductive groups such as sulfonates, or non-ionic conductive groups such as glycerol, or copolymers of the monomers with other monomers (for example, polymers having ionic conductivity such as polymers having structural units derived from acrylates or methacrylates having quaternary ammonium salt groups); materials obtained by alloying hydrophilic polymers such as copolymers of ethylene and methacrylates with acrylic resins, etc. (permanent antistatic agents).

[0120] The conductive layer 40 may contain other materials such as adhesives in addition to the conductive material. The adhesive has a tendency to improve the film-forming property of the conductive material and to improve the adhesion and bonding (anchoring force) of the conductive layer 40 to the polarizing film 20. Examples of the adhesive include: Oxazoline polymers, polyurethane resins, polyester resins, acrylic resins, polyether resins, cellulose resins, polyvinyl alcohol resins, epoxy resins, polyvinyl pyrrolidone, polystyrene resins, polyethylene glycol, pentaerythritol, etc., preferably containing The conductive layer 40 may contain one or more of these adhesives. The content of the adhesive in the conductive layer 40 is, for example, 1 wt% to 90 wt%, preferably 10 wt% to 80 wt%.

[0121] The thickness of the conductive layer 40 is, for example, 5 nm to 180 nm, preferably 150 nm, more preferably 120 nm or less, further preferably 100 nm or less, particularly preferably 80 nm or less, and particularly preferably 50 nm or less. The thickness of the conductive layer 40 may be 10 nm or more, or 20 nm or more.

[0122] In the polarizing film 15 with an anti-reflection film, the total light transmittance loss A caused by the conductive layer 40 is, for example, 0.9% or less, preferably 0.8% or less, more preferably 0.6% or less, further preferably 0.5% or less, particularly preferably 0.4% or less, and particularly preferably less than 0.2%. The lower limit of the loss A is not particularly limited, and is, for example, 0.01%. The loss A can be specified by the following method. First, the total light transmittance T1 of the polarizing film 20 and the total light transmittance T2 of the laminate L including the polarizing film 20 and the conductive layer 40 are measured. The total light transmittance T2 of the laminate L is the value when light is incident from the polarizing film 20 side. The difference (T1-T2) between the total light transmittance T1 and the total light transmittance T2 can be specified as the loss A.

[0123] In the case where the loss A is greater than 0.5% in the polarizing film 15 with an anti-reflection film, the surface resistivity of the conductive layer 40 can be a particularly low value. As an example, in the polarizing film 15 with an anti-reflection film, at least one of the following (i) and (ii) can be satisfied: (i) the loss A is less than 0.5% and the surface resistivity of the conductive layer 40 is 1.0×10 6 Ω / □ or less; and (ii) the above-mentioned loss A is less than 0.9%, and the surface resistivity of the conductive layer 40 is 1.0×10 4 Ω / □ or less.

[0124] The anchoring force between the conductive layer 40 and the polarizing film 20 is, for example, 10.0 N / 25 mm or more, preferably 12.0 N / 25 mm or more, more preferably 14.0 N / 25 mm or more, and further preferably 18.0 N / 25 mm or more. The above-mentioned anchoring force can be measured by the following method. First, the polarizing film 15 with an anti-reflection film as the evaluation object is cut into a 25 mm wide × 150 mm long piece as a test piece. Next, use double-sided tape to overlap the entire surface of the anti-reflection film 10 of the test piece with a stainless steel test plate, and press them together by reciprocating a 2 kg roller once. Next, overlap the adhesive layer 30 of the test piece with the evaluation piece, and press them together by reciprocating a 2 kg roller once. The evaluation piece has a size of 30 mm wide × 150 mm long, and there is no special limitation as long as it does not peel off from the adhesive layer 30 during the test. As an evaluation sheet, for example, an ITO film (125Tetlight OES (manufactured by Oike Industries, Ltd.) etc.) can be used. Next, using a commercially available tensile testing machine, while holding the evaluation sheet, the adhesive layer 30 and the conductive layer 40 are peeled off from the polarizing film 20 at a peeling angle of 180° and a tensile speed of 300 mm / min, and the average value of the peeling force at this time is specified as the anchoring force between the conductive layer 40 and the polarizing film 20. It should be noted that the above test was carried out in an atmosphere of 23°C.

[0125] [Adhesive layer]

[0126] The adhesive layer 30 is a layer containing an adhesive. Examples of the adhesive contained in the adhesive layer 30 include rubber adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl pyrrolidone adhesives, polyacrylamide adhesives, and cellulose adhesives. As the adhesive contained in the adhesive layer 30, an acrylic adhesive is preferred from the viewpoints of excellent optical transparency, appropriate adhesive properties such as wettability, cohesiveness, and adhesion, and excellent weather resistance, heat resistance, and the like.

[0127] The acrylic adhesive contains a (meth) acrylic polymer as a base polymer. The (meth) acrylic polymer contains, for example, a structural unit derived from a (meth) acrylic ester as a main component. In this specification, "(meth) acrylic acid" refers to acrylic acid and / or methacrylic acid. "Main component" refers to the structural unit with the largest content in the polymer on a weight basis.

[0128] The number of carbon atoms in the ester portion (the portion other than the (meth)acryloyl group) contained in the (meth)acrylate used to form the main skeleton of the (meth)acrylic polymer is not particularly limited, and is, for example, 1 to 18. The ester portion of the (meth)acrylate may contain an aromatic ring such as a phenyl group or a phenoxy group, and may also contain an alkyl group. The alkyl group may be linear or branched. The (meth)acrylic polymer may contain one or more structural units derived from (meth)acrylate. In the (meth)acrylic polymer, the average value of the number of carbon atoms in the ester portion contained in the structural unit derived from (meth)acrylate is preferably 3 to 9. From the viewpoints of adhesive properties, durability, adjustment of phase difference, adjustment of refractive index, etc., the (meth)acrylic polymer preferably has a structural unit derived from a (meth)acrylate containing an aromatic ring. By adjusting the phase difference of the adhesive layer 30 by a (meth)acrylate containing an aromatic ring, it is possible to suppress light leakage of the liquid crystal display device caused by the stretching of the adhesive layer 30 due to the thermal shrinkage of the polarizing film 20. In addition, the (meth)acrylate is suitable for adjusting the refractive index of the adhesive layer 30 to reduce the difference in refractive index between the adhesive layer 30 and the adherend (liquid crystal cell). If the difference in refractive index is reduced, the reflection of light at the interface between the adhesive layer 30 and the adherend is suppressed, and the visual recognition of the display can be improved.

[0129] Examples of the (meth)acrylate containing an aromatic ring include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified nonylphenol (meth)acrylate, ethylene oxide-modified cresol (meth)acrylate, phenol ethylene oxide-modified (meth)acrylate, 2-hydroxy (meth)acrylate, (Meth)acrylates containing benzene rings, such as β-phenoxypropyl acrylate, methoxybenzyl (meth)acrylate, benzyl (meth)acrylate chloride, toluene (meth)acrylate, and styrene (meth)acrylate; (meth)acrylates containing naphthalene rings, such as hydroxyethylated β-naphthol acrylate, 2-naphthylethyl (meth)acrylate, 2-naphthyloxyethyl acrylate, and 2-(4-methoxy-1-naphthyloxy)ethyl (meth)acrylate; (meth)acrylates containing biphenyl rings, such as biphenyl (meth)acrylate, etc. Among these, benzyl (meth)acrylate and phenoxyethyl (meth)acrylate are preferred from the viewpoint of improving the adhesive properties and durability of the adhesive layer 30.

[0130] In the case where the refractive index of the adhesive layer 30 is adjusted by a (meth)acrylate containing an aromatic ring, the content of the structural unit derived from the (meth)acrylate containing an aromatic ring in all the constituent units of the (meth)acrylic polymer is preferably 3% by weight to 25% by weight. The content is more preferably 22% by weight or less, and further preferably 20% by weight or less. The content is more preferably 8% by weight or more, and further preferably 12% by weight or more. When the content of the structural unit derived from the (meth)acrylate containing an aromatic ring is 25% by weight or less, there is a tendency to suppress the light leakage of the liquid crystal display device caused by the shrinkage of the polarizing film 20 and to improve the reoperability of the adhesive layer 30. When the content is 3% by weight or more, there is a tendency to fully suppress the light leakage of the liquid crystal display device.

[0131] From the viewpoint of improving adhesion and heat resistance, the (meth)acrylic polymer may have, in addition to the above-mentioned structural units derived from the (meth)acrylate containing an aromatic ring, one or more structural units derived from a comonomer having a polymerizable functional group containing an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. Examples of the comonomer include: hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl acrylate; carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride; caprolactone adducts of acrylic acid; sulfonic acid group-containing monomers such as styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, propyl (meth)acrylate sulfonate, and (meth)acryloyloxynaphthalenesulfonic acid; phosphoric acid group-containing monomers such as 2-hydroxyethylacryloyl phosphate, and the like.

[0132] Examples of the above-mentioned comonomers include (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methylolpropane (meth)acrylamide and other (N-substituted)amide monomers; (meth)acrylic acid alkylaminoalkyl ester monomers such as (meth)aminoethyl acrylate, (meth)acrylic acid N,N-dimethylaminoethyl ester, (meth)acrylic acid tert-butylaminoethyl ester; (meth)acrylic acid alkoxyalkyl ester monomers such as (meth)methoxyethyl acrylate, (meth)ethoxyethyl acrylate; N-(meth)acrylic acid Succinimide monomers such as acyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyoctamethylene succinimide; morpholine monomers such as N-acryloylmorpholine; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide.

[0133] Examples of the comonomers include vinyl acetate, vinyl propionate, N-vinyl pyrrolidone, methyl vinyl pyrrolidone, vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl Vinyl monomers such as oxazole, vinyl morpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, N-vinyl caprolactam, etc.; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; diol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate; acrylate monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine-containing (meth)acrylate, silicone (meth)acrylate, 2-methoxyethyl acrylate, etc. In addition, as comonomers, olefin monomers such as isoprene, butadiene, isobutylene, etc.; ether group-containing vinyl monomers such as vinyl ether.

[0134] As the above-mentioned comonomers, for example, silane monomers such as 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloxydecyltrimethoxysilane, 10-acryloxydecyltrimethoxysilane, 10-methacryloxydecyltriethoxysilane, and 10-acryloxydecyltriethoxysilane can also be mentioned.

[0135] As the above-mentioned comonomer, for example, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and the like can be used. Esterification products of (meth)acrylic acid and polyols such as acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate (multifunctional monomers having two or more unsaturated double bonds such as (meth)acryloyl groups and vinyl groups); compounds obtained by adding two or more compounds having unsaturated double bonds such as (meth)acryloyl groups and vinyl groups to the backbones of polyester, epoxy, urethane, etc. (for example, polyester (meth)acrylate, epoxy (meth)acrylate and urethane (meth)acrylate), etc.

[0136] The content of the structural unit derived from the comonomer in the (meth)acrylic polymer is not particularly limited, and is, for example, 0 wt % to 20 wt %, preferably 0.1 wt % to 15 wt %, and more preferably 0.1 wt % to 10 wt %.

[0137] As comonomers, hydroxyl-containing monomers and carboxyl-containing monomers are preferred from the viewpoint of adhesion and durability. As comonomers, hydroxyl-containing monomers and carboxyl-containing monomers can also be used in combination. For example, when the adhesive composition used to form the adhesive layer 30 contains a crosslinking agent, the comonomer functions as a reaction point with the crosslinking agent. As hydroxyl-containing monomers, carboxyl-containing monomers, etc., they are suitable for improving the cohesion and heat resistance of the obtained adhesive layer 30 due to their excellent reactivity with intermolecular crosslinking agents. In particular, hydroxyl-containing monomers are suitable for improving the reoperability of the adhesive layer 30. Carboxyl-containing monomers are suitable for taking into account both the durability and reoperability of the adhesive layer 30.

[0138] When a hydroxyl group-containing monomer is used as a comonomer, the content of the structural unit derived from the hydroxyl group-containing monomer in the (meth)acrylic polymer is preferably 0.01 wt% to 15 wt%, more preferably 0.03 wt% to 10 wt%, and further preferably 0.05 wt% to 7 wt%. When a carboxyl group-containing monomer is used as a comonomer, the content of the structural unit derived from the carboxyl group-containing monomer in the (meth)acrylic polymer is preferably 0.05 wt% to 10 wt%, more preferably 0.1 wt% to 8 wt%, and further preferably 0.2 wt% to 6 wt%.

[0139] The weight average molecular weight of the (meth)acrylic polymer is, for example, 500,000 to 3,000,000. From the viewpoint of durability, especially heat resistance, it is preferably 700,000 to 2,700,000, and more preferably 800,000 to 2,500,000. When the weight average molecular weight of the (meth)acrylic polymer is 500,000 or more, the adhesive layer 30 tends to have sufficient heat resistance for practical use. When the weight average molecular weight of the (meth)acrylic polymer is 3,000,000 or less, there is a tendency that the viscosity of the coating liquid used to make the adhesive layer 30 can be easily adjusted. If the viscosity of the coating liquid can be easily adjusted, it is not necessary to add a large amount of dilution solvent to the coating liquid, and therefore, the manufacturing cost of the adhesive layer 30 can be suppressed. In this specification, the weight average molecular weight refers to the value obtained by converting the measurement results based on GPC (gel permeation chromatography) into polystyrene.

[0140] The (meth)acrylic polymer can be produced by known polymerization reactions such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The (meth)acrylic polymer may be a random copolymer, a block copolymer, or a graft copolymer.

[0141] The adhesive contained in the adhesive layer 30 may have a structure in which a base polymer is cross-linked by a cross-linking agent. For example, when a (meth) acrylic polymer is used as a base polymer, an organic cross-linking agent or a multifunctional metal chelate may be used as a cross-linking agent. As an organic cross-linking agent, for example, isocyanate cross-linking agents, peroxide cross-linking agents, epoxy cross-linking agents, imine cross-linking agents, etc. may be mentioned. A multifunctional metal chelate refers to a chelate formed by covalent bonding or coordinated bonding of a polyvalent metal to an organic compound. As atoms constituting the polyvalent metal, for example, Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, Ti, etc. may be mentioned. The organic compound contained in the multifunctional metal chelate may contain, for example, oxygen atoms, etc. As the organic compound, for example, alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, ketone compounds, etc. may be mentioned.

[0142] In the pressure-sensitive adhesive, the amount of the crosslinking agent used is preferably 3 parts by weight or less, more preferably 0.01 to 3 parts by weight, further preferably 0.02 to 2 parts by weight, particularly preferably 0.03 to 1 part by weight, based on 100 parts by weight of the (meth)acrylic polymer.

[0143] The adhesive layer 30 may further include other materials other than the adhesive. As other materials, for example, conductive materials, silane coupling agents and other additives can be cited. The conductive material is suitable for reducing the surface resistivity of the adhesive layer 30 to prevent poor display caused by charging of the liquid crystal display device. As the conductive material, the conductive materials described above for the conductive layer 40 can be cited. From the viewpoint of compatibility with the base polymer and the transparency of the adhesive layer 30, the conductive material contained in the adhesive layer 30 is preferably an ionic compound. In particular, when the adhesive layer 30 includes an acrylic adhesive containing a (meth) acrylic polymer as a base polymer, an ionic compound is preferably used as the conductive material. From the viewpoint of antistatic performance, the ionic compound is preferably an ionic liquid.

[0144] The adhesive layer 30 preferably contains 0.05 to 20 parts by weight of a conductive material (e.g., an ionic compound) relative to 100 parts by weight of the base polymer of the adhesive (e.g., a (meth) acrylic polymer). By making the adhesive layer 30 contain 0.05 parts by weight or more of a conductive material, there is a tendency that the surface resistivity of the adhesive layer 30 is sufficiently reduced and the antistatic performance of the adhesive layer 30 is sufficiently improved. The adhesive layer 30 preferably contains 0.1 parts by weight or more of a conductive material relative to 100 parts by weight of the base polymer of the adhesive, and more preferably contains 0.5 parts by weight or more. From the viewpoint of giving the adhesive layer 30 sufficient durability for practical use, the adhesive layer 30 preferably contains 20 parts by weight or less of a conductive material relative to 100 parts by weight of the base polymer of the adhesive, and more preferably contains 10 parts by weight or less.

[0145] As other additives, for example, polyether compounds such as polyalkylene glycol (such as polypropylene glycol), colorants, pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic fillers, organic fillers, metal powders, etc. can be appropriately used according to the use purpose. The additive can be a powder, or it can be in a particle shape, or it can be in a foil shape. As an additive, it is also possible to form a redox class by using a reducing agent within a controllable range. By adding pigments such as colorants to the adhesive layer 30, it is sometimes possible to adjust the hue of the reflected light from the liquid crystal panel 100. Relative to 100 parts by weight of the base polymer (such as (methyl) acrylic polymer) of the adhesive, the adhesive layer 30 preferably contains less than 5 parts by weight of other additives, more preferably less than 3 parts by weight, and further preferably less than 1 part by weight.

[0146] The thickness of the adhesive layer 30 is not particularly limited, and is, for example, 5 to 100 μm, and preferably 10 to 50 μm.

[0147] In the polarizing film with an antireflection film 15, the surface resistivity of the adhesive layer 30 is not particularly limited, but is less than 1.0×10 14 Ω / □, preferably 1.0×10 12 Ω / □ or less. The lower limit of the surface resistivity of the adhesive layer 30 is not particularly limited, but is, for example, 1.0×10 8 Ω / □. The surface resistivity of the adhesive layer 30 can be measured by the following method. First, a laminate in which the surface of the adhesive layer 30 is exposed to the outside is prepared. As such a laminate, for example, there can be mentioned: a laminate in which the adhesive layer 30 is arranged on a separator such as a polyethylene terephthalate film. Next, the surface resistivity of the surface of the adhesive layer 30 in the prepared laminate is measured. The surface resistivity can be measured using Hiresta-UP MCP-HT450 (manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and according to the method specified in JIS K6911:1995. The measured value obtained by this measurement can be regarded as the surface resistivity of the adhesive layer 30.

[0148] [Other layers]

[0149] The polarizing film 15 with an anti-reflection film may further include other layers other than the anti-reflection film 10, the polarizing film 20, the conductive layer 40, and the adhesive layer 30. The polarizing film 15 with an anti-reflection film may include one or more other layers. For example, the other layer is arranged closer to the visible side than the anti-reflection film 10 and is in contact with the anti-reflection film 10. Examples of the other layer include: a surface protection film and a phase difference film.

[0150] The surface protection film, for example, comprises a support film and an adhesive layer disposed on at least one side of the support film. The adhesive layer of the surface protection film may contain a light release agent, a conductive material, etc. In the case where the adhesive layer of the surface protection film contains a conductive material, the surface protection film can be adhered to the anti-reflection film 10 and then the surface protection film is peeled off, so that the anti-reflection film 10 contains a conductive material, and a conductive function is imparted to the surface. As the conductive material, the conductive materials described above to the conductive layer 40 can be cited. In order to impart a conductive function to the surface of the anti-reflection film 10 by peeling off the surface protection film, it is preferred that the adhesive layer of the surface protection film also contains a light release agent while containing the conductive material. As the light release agent, for example, silicone resins such as polyorganosiloxane can be cited. The conductive function imparted to the surface of the anti-reflection film 10 can be appropriately adjusted by the amount of the conductive material and the light release agent.

[0151] The other layers may include an easy-adhesion layer for improving the adhesion between the components. When the other layers are easy-adhesion layers, the easy-adhesion layers may be disposed on the surface of the polarizing film 20. It should be noted that the surface of the polarizing film 20 may be subjected to an easy-adhesion treatment such as a corona treatment or a plasma treatment instead of the easy-adhesion layer.

[0152] [Method for producing polarizing film with anti-reflection film]

[0153] The polarizing film 15 with an antireflection film having a conductive layer 40 can be produced, for example, by the following method. First, a solution or dispersion of a conductive material is prepared. The solvent of the solution or dispersion is, for example, water, and may further contain a water-soluble organic solvent. Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, tert-pentanol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, and cyclohexanol.

[0154] Next, a solution or dispersion of a conductive material is applied to the surface of the polarizing film 20. The obtained coating film is dried to form the conductive layer 40 on the polarizing film 20. Thus, a laminate L including the polarizing film 20 and the conductive layer 40 can be obtained.

[0155] Next, an anti-reflection film 10 (or 11) is arranged on the polarizing film 20 of the stack L to produce the stack L1. Next, a solution containing an adhesive is prepared. A coating film is obtained by applying the solution to the surface of the diaphragm. The diaphragm is not particularly limited, for example, a polyethylene terephthalate film treated with a silicone-based release agent can be used. Next, an adhesive layer 30 is formed on the diaphragm by drying the coating film. By transferring the obtained adhesive layer 30 to the conductive layer 40 of the stack L1, a polarizing film 15 with an anti-reflection film can be produced.

[0156] [Liquid crystal unit]

[0157] The liquid crystal cell 25 includes, for example, a liquid crystal layer 50, a first transparent substrate 60, and a second transparent substrate 70. The liquid crystal layer 50 is, for example, disposed between the first transparent substrate 60 and the second transparent substrate 70 and is in contact with the first transparent substrate 60 and the second transparent substrate 70, respectively. The adhesive layer 30 of the polarizing film with an anti-reflection film 15 is, for example, in contact with the first transparent substrate 60 of the liquid crystal cell 25. The liquid crystal panel 100 does not include an ITO layer between the adhesive layer 30 and the first transparent substrate 60, for example.

[0158] The liquid crystal layer 50 includes, for example, liquid crystal molecules that are uniformly oriented in the absence of an electric field. The liquid crystal layer 50 including such liquid crystal molecules is suitable for an IPS (In-Plane-Switching) method. However, the liquid crystal layer 50 can also be used for a TN (Twisted Nematic) type, an STN (Super Twisted Nematic) type, a π type, a VA (Vertical Alignment) type, etc. The thickness of the liquid crystal layer 50 is, for example, 1.5 μm to 4 μm.

[0159] As materials of the first transparent substrate 60 and the second transparent substrate 70, for example, glass and polymers can be cited. In this specification, a transparent substrate composed of a polymer is sometimes referred to as a polymer film. As polymers constituting the transparent substrate, for example, polyethylene terephthalate, polycycloolefin, polycarbonate, etc. can be cited. The thickness of the transparent substrate composed of glass is, for example, 0.1 mm to 1 mm. The thickness of the transparent substrate composed of a polymer is, for example, 10 μm to 200 μm.

[0160] The liquid crystal cell 25 may further include other layers other than the liquid crystal layer 50, the first transparent substrate 60, and the second transparent substrate 70. Examples of other layers include a color filter, an easy-adhesion layer, and a hard coating layer. The color filter is, for example, disposed closer to the visible side than the liquid crystal layer 50, preferably between the first transparent substrate 60 and the adhesive layer 30 of the polarizing film 15 with an anti-reflection film. The easy-adhesion layer and the hard coating layer are, for example, disposed on the surface of the first transparent substrate 60 or the second transparent substrate 70.

[0161] [Other components]

[0162] The liquid crystal panel 100 may further include a polarizing film 15 with an anti-reflection film and other components other than the liquid crystal unit 25. For example, the liquid crystal panel 100 may further include a conductive structure (not shown) electrically connected to the side of the polarizing film 15 with an anti-reflection film. If the conductive structure is connected to the ground, it is easy to suppress the polarizing film 15 with an anti-reflection film from being charged by static electricity. The conductive structure may cover the entire side of the polarizing film 15 with an anti-reflection film, or may partially cover the side of the polarizing film 15 with an anti-reflection film. The ratio of the area of ​​the side of the polarizing film 15 with an anti-reflection film covered by the conductive structure to the area of ​​the entire side of the polarizing film 15 with an anti-reflection film is, for example, 1% or more, preferably 3% or more.

[0163] Examples of the material of the conductive structure include conductive pastes made of metals such as silver and gold, conductive adhesives, and other conductive materials. The conductive structure may be wiring extending from the side surface of the polarizing film 15 with an antireflection film.

[0164] The liquid crystal panel 100 may further include other optical films other than the polarizing film 20. Examples of other optical films include polarizing films, reflective plates, anti-transmission plates, phase difference films, viewing angle compensation films, brightness enhancement films, and other films used in liquid crystal display devices. Phase difference films include, for example, 1 / 2 wave plates, 1 / 4 wave plates, and the like. The liquid crystal panel 100 may further include one or more other optical films among these.

[0165] When the other optical film is a polarizing film, the polarizing film is bonded to the second transparent substrate 70 of the liquid crystal cell 25 via an adhesive layer, for example. The polarizing film has, for example, the structure described above for the polarizing film 20. In the polarizing film as the other optical film, the transmission axis (or absorption axis) of the polarizer is, for example, orthogonal to the transmission axis (or absorption axis) of the polarizer in the polarizing film 20. As the material of the adhesive layer for bonding the polarizing film to the second transparent substrate 70, the material described above for the adhesive layer 30 can be used. The thickness of the adhesive layer is not particularly limited, and is, for example, 1 to 100 μm, preferably 2 to 50 μm, more preferably 2 to 40 μm, and further preferably 5 to 35 μm.

[0166] According to the liquid crystal panel 100 of the present embodiment, the surface resistivity of the conductive layer 40 of the polarizing film 15 with an anti-reflection film is adjusted to 1.0×10 6Ω / □ or less, even in an environment where static electricity is easily generated, poor display caused by the charging of the liquid crystal display device can be prevented. For example, the liquid crystal panel 100 shows good results when an ESD (electrostatic discharge, Electro-Static Discharge) test is performed. The ESD test is implemented, for example, by the following method. First, the liquid crystal panel 100 is set on a backlight device. Next, static electricity is applied to the visible side (anti-reflection film 10 side) of the liquid crystal panel 100. Static electricity is applied using an electrostatic discharge gun (Electrostatic discharge Gun) whose applied voltage is adjusted to 10kV. When static electricity is applied, white spots appear on a part of the liquid crystal panel 100. The time T from the time the static electricity is applied until the white spots disappear is measured. For the liquid crystal panel 100, the time T is, for example, less than 10 seconds, preferably less than 1 second, and more preferably less than 0.5 seconds. It should be noted that the ESD test is carried out under the conditions of 23°C and 55% RH.

[0167] The inventors of the present invention have newly discovered that by adopting a structure in which a conductive layer such as an ITO layer is not provided between the polarizing film 15 with an anti-reflection film and the liquid crystal unit 25, the reflection of light in the liquid crystal panel 100 can be greatly suppressed. The liquid crystal panel 100 is suitable for applications requiring good visual recognition, especially for vehicle-mounted displays. As vehicle-mounted displays, for example, there can be cited: instrument panels for car navigation devices, instrument panel clusters, mirror displays, etc. The instrument panel cluster is a panel that displays the vehicle's driving speed, engine speed, etc. The liquid crystal panel 100 is particularly suitable for applications that do not require a touch sensor, such as instrument panel clusters and mirror displays.

[0168] (Modification of Liquid Crystal Panel)

[0169] The polarizing film with an anti-reflection film 15 provided in the liquid crystal panel 100 may further include other components other than the above components. Figure 4 As shown, in the liquid crystal panel 110 of this modified example, the polarizing film 16 with an anti-reflection film further has a transparent substrate 45 and an adhesive layer 46 disposed between the anti-reflection film 10 and the polarizing film 20. Except for the transparent substrate 45 and the adhesive layer 46, the structure of the liquid crystal panel 110 is the same as that of the liquid crystal panel 100. Therefore, the same reference symbols are marked for the common elements in the liquid crystal panel 100 and the liquid crystal panel 110 of the modified example, and their descriptions are sometimes omitted. That is, the descriptions related to the following embodiments can be applied to each other as long as they are not technically contradictory. The following embodiments can also be combined with each other as long as they are not technically contradictory.

[0170] The transparent substrate 45 is in contact with the first high refractive index layer 1 of the antireflection film 10, for example. However, the polarizing film 16 with an antireflection film may also have Figure 3The anti-reflection film 11 described in the above is used instead of the anti-reflection film 10. At this time, the adhesive layer 6 of the anti-reflection film 11 is in contact with the transparent substrate 45. The adhesive layer 46 is, for example, disposed between the transparent substrate 45 and the polarizing film 20 and in contact with the transparent substrate 45 and the polarizing film 20, respectively.

[0171] As the transparent substrate 45, the transparent substrates described above for the first transparent substrate 60 and the second transparent substrate 70 can be used, and are preferably made of glass. In this specification, the transparent substrate 45 made of glass may be referred to as "cover glass".

[0172] As the adhesive layer 46, the adhesive layer described above for the adhesive layer 30 can be used. It is particularly preferred that the adhesive layer 46 includes a commercially available optically clear adhesive (OCA). The adhesive layer 46 can be formed using, for example, an adhesive tape such as LUCIACS (registered trademark) CS9621T.

[0173] (Another Modification of Liquid Crystal Panel)

[0174] The liquid crystal panel 100 or 110 may further include a touch sensor or a touch panel. Figure 5 The liquid crystal panel 120 is shown to include the touch panel 80 . The structure of the liquid crystal panel 120 is the same as that of the liquid crystal panel 100 except for the touch panel 80 .

[0175] In the liquid crystal panel 120, the touch panel 80 is, for example, arranged closer to the visible side than the anti-reflection film 10. The touch panel 80 is not in contact with the polarizing film 15 with the anti-reflection film, and a gap (air layer) is formed between the touch panel 80 and the polarizing film 15 with the anti-reflection film. The liquid crystal panel 120 is a so-called out-cell type liquid crystal panel. As the touch panel 80, an optical method, an ultrasonic method, an electrostatic capacitance method, a resistive film method, etc. can be adopted. In the case where the touch panel 80 is a resistive film method, the touch panel 80 has, for example, a structure in which two electrode plates having a transparent conductive film are arranged in a manner opposite to each other with a spacer therebetween. In the case where the touch panel 80 is a capacitive method, the touch panel 80 is, for example, composed of a transparent conductive film having a transparent conductive film having a given pattern shape.

[0176] (Embodiment of Liquid Crystal Display Device)

[0177] The liquid crystal display device of this embodiment includes, for example, a liquid crystal panel 100 and a lighting system. In the liquid crystal display device, the liquid crystal panel 110 or 120 may be used instead of the liquid crystal panel 100. In the liquid crystal display device, the liquid crystal panel 100 is, for example, arranged closer to the visible side than the lighting system. The lighting system includes, for example, a backlight or a reflector, and irradiates light to the liquid crystal panel 100.

[0178] Example

[0179] The present invention is described in more detail below by way of examples. The present invention is not limited to the examples shown below. It should be noted that, below, unless otherwise specified, "%" means "weight %", "parts" means "parts by weight", and "thickness" means "physical film thickness". Unless otherwise specified, the indoor temperature and humidity are 23°C and 65%RH.

[0180] <Weight average molecular weight of (meth)acrylic polymer>

[0181] In the following examples, the weight average molecular weight (Mw) of the (meth)acrylic polymer was measured by GPC (gel permeation chromatography). Mw / Mn of the (meth)acrylic polymer was also measured in the same manner.

[0182] ·Analysis device: Made by Tosoh Corporation, HLC-8120GPC

[0183] ·Chromatographic column: G7000H manufactured by Tosoh Corporation XL +GMH XL +GMH XL

[0184] Column size: 7.8mmφ×30cm, total 90cm

[0185] Column temperature: 40℃

[0186] Flow rate: 0.8mL / min

[0187] Injection volume: 100μL

[0188] ·Eluent: Tetrahydrofuran

[0189] Detector: Differential Refractometer (RI)

[0190] Standard sample: polystyrene

[0191] <Adhesive layer A>

[0192] First, a monomer mixture was obtained by adding 76.9 parts of butyl acrylate, 18 parts of benzyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 4-hydroxybutyl acrylate to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts of the monomer mixture (solid content). While slowly stirring the mixture, nitrogen was introduced into the flask to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C and a polymerization reaction was performed for 8 hours, thereby preparing a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2 million and Mw / Mn=4.1.

[0193] Next, 0.45 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), 0.1 parts of a peroxide crosslinking agent (NYPER BMT manufactured by NOF Corporation), and 0.2 parts of a silane coupling agent (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropylmethoxysilane) were further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0194] Next, the obtained solution was applied to one side of a separator (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.). The separator was a polyethylene terephthalate film treated with a silicone release agent. The obtained coating film was dried at 155° C. for 1 minute to form an adhesive layer A on the surface of the separator. The thickness of the adhesive layer A was 20 μm.

[0195] <Adhesive layer B>

[0196] Adhesive layer B was produced in the same manner as Adhesive layer A except that 1 part of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, manufactured by Mitsubishi Materials Corporation) was further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0197] <Adhesive layer C>

[0198] First, 94.9 parts of butyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 4-hydroxybutyl acrylate were added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser to obtain a monomer mixture. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts of ethyl acetate to 100 parts of the monomer mixture (solid content). While slowly stirring the mixture, nitrogen was introduced into the flask to replace the nitrogen. The liquid temperature in the flask was maintained at about 55°C and the polymerization reaction was carried out for 8 hours, thereby preparing a solution of an acrylic polymer with a weight average molecular weight (Mw) of 2.1 million and Mw / Mn=4.0.

[0199] Next, 0.45 parts of an isocyanate crosslinking agent (Coronate L manufactured by Tosoh Corporation, trimethylolpropane toluene diisocyanate), 0.1 parts of a peroxide crosslinking agent (NYPER BMT manufactured by NOF Corporation), and 0.2 parts of a silane coupling agent (KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd., γ-glycidoxypropylmethoxysilane) were further added to 100 parts of the solid content of the acrylic polymer solution to prepare a solution of an acrylic adhesive composition.

[0200] Next, the obtained solution was applied to one side of a separator (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.). The separator was a polyethylene terephthalate film treated with a silicone release agent. The obtained coating film was dried at 155° C. for 1 minute to form an adhesive layer C on the surface of the separator. The thickness of the adhesive layer C was 12 μm.

[0201] <Anti-reflective film AR1>

[0202] First, as resins for forming an anti-glare layer, 50 parts by weight of an ultraviolet-curable urethane acrylate resin (manufactured by Mitsubishi Chemical Corporation, trade name "UV1700TL", solid content concentration 80% by weight) and 50 parts by weight of a multifunctional acrylate containing pentaerythritol triacrylate as a main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat#300", solid content concentration 100% by weight) were prepared. For every 100 parts by weight of the solid content of these resins, 4 parts by weight of particles of a copolymer of (meth)acrylate and styrene (manufactured by Sekisui Chemicals Co., Ltd., trade name "Techpolymer SSX504TNR", weight average particle size: 3.0 μm), 1.5 parts by weight of an organic clay as a thixotropy imparting agent, i.e., synthetic montmorillonite (manufactured by Kunimine Industries Co., Ltd., trade name "Smekton SAN"), 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907"), and 0.015 parts by weight of a leveling agent (manufactured by DIC Corporation, trade name "GRANDIC PC4100", solid content concentration 10% by weight) were mixed. The mixture was diluted with a toluene / cyclopentanone mixed solvent (weight ratio 80 / 20) so that the solid content concentration became 50% by weight, thereby preparing a material (coating liquid) for forming an anti-glare layer.

[0203] Next, a triacetylcellulose (TAC) film (manufactured by Fuji Film Co., Ltd., trade name "TD60UL") was prepared. A material (coating liquid) for forming an anti-glare layer was applied to one side of the transparent plastic film (TAC film) using a wire bar coater to form a coating film. Next, the transparent plastic film with the coating film was heated at 80°C for 1 minute to dry the coating film. Next, the coating film was irradiated with a high-pressure mercury lamp with a cumulative light intensity of 300 mJ / cm 2 The TAC film with an antiglare layer having an antiglare layer thickness of 8.0 μm was obtained. The haze of the TAC film with an antiglare layer was 8%.

[0204] Next, the TAC film with the anti-glare layer was introduced into a roll-to-roll sputtering film forming device and the film was allowed to travel, thereby bombarding the surface of the anti-glare layer (using Ar gas plasma treatment). Next, a SiO2 film with a physical film thickness of 3 nm was formed on the surface of the anti-glare layer as a bonding layer. xLayer (x<2). Next, a Nb2O5 layer (first high refractive index layer) with a physical film thickness of 12nm, a SiO2 layer (first low refractive index layer) with a physical film thickness of 29nm, a Nb2O5 layer (second high refractive index layer) with a physical film thickness of 116nm, and a SiO2 layer (second low refractive index layer) with a physical film thickness of 78nm were sequentially formed on the adhesion layer to produce a laminate a. When forming these oxide thin films, the pressure in the device was kept constant by adjusting the introduction and exhaust volume of argon gas, and the amount of oxygen introduced was adjusted by plasma glow emission monitoring (PEM) control.

[0205] Next, a layer (physical film thickness: 9 nm) made of a fluorine-based resin as an antifouling layer was formed on the surface of the second low refractive index layer (SiO2 layer) of the laminate a. The adhesive layer C was further transferred to the surface of the TAC film of the laminate a to prepare an antireflection film AR1.

[0206] <Anti-reflection film AR2~AR10>

[0207] Except that the physical film thickness of each layer was changed to the value shown in Table 1, the antireflection films AR2 to AR10 were produced by the same method as the antireflection film AR1.

[0208] [Table 1]

[0209]

[0210] <Polarizing film P1>

[0211] First, an acrylic film was prepared by the following method. 8000 g of methyl methacrylate (MMA), 2000 g of methyl 2-(hydroxymethyl)acrylate (MHMA), 10000 g of 4-methyl-2-pentanone (methyl isobutyl ketone, MIBK), and 5 g of n-dodecyl mercaptan were added to a 30 L kettle reactor equipped with a stirring device, a temperature sensor, a condenser, and a nitrogen inlet pipe. While introducing nitrogen into the reactor, the mixture in the reactor was heated to 105°C and refluxed. Next, 5.0 g of tert-butyl peroxyisopropyl carbonate (Kayakarubon BIC-7, manufactured by KayakuAkzo Co., Ltd.) was added as a polymerization initiator, and a solution made of 10.0 g of tert-butyl peroxyisopropyl carbonate and 230 g of MIBK was dripped over 4 hours to perform solution polymerization. Solution polymerization was performed at about 105 to 120°C under reflux. After the solution was dripped, it was further aged for 4 hours.

[0212] Next, 30 g of a mixture of stearyl phosphate / distearyl phosphate (Phoslex A-18, manufactured by Sakai Chemical Industry) was added to the obtained polymer solution, and a cyclocondensation reaction was carried out at about 90 to 120° C. for 5 hours under reflux. Next, the obtained solution was introduced into a vented twin-screw extruder (φ=29.75 mm, L / D=30) with a barrel temperature of 260° C., a rotation speed of 100 rpm, a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), 1 rear vent hole, and 4 front vent holes at a processing rate of 2.0 kg / h according to the resin amount. Further cyclocondensation reaction and devolatilization were carried out in the extruder. Thus, transparent particles of a lactone ring-containing polymer were obtained.

[0213] The obtained lactone ring-containing polymer was subjected to dynamic TG measurement, and a mass loss of 0.17 mass % was detected. The lactone ring-containing polymer had a weight average molecular weight of 133,000, a melt flow rate of 6.5 g / 10 min, and a glass transition temperature of 131°C.

[0214] The obtained pellets were kneaded and extruded with acrylonitrile-styrene (AS) resin (ToyoAS AS20, manufactured by Toyo Styrene Co., Ltd.) at a mass ratio of 90 / 10 using a single screw extruder (screw 30 mmφ) to obtain transparent pellets. The obtained pellets had a glass transition temperature of 127°C.

[0215] The pellets were melt-extruded from a 400 mm wide coat hanger T die using a 50 mm φ single screw extruder to produce a 120 μm thick film. The film was stretched to 2.0 times in the longitudinal direction and 2.0 times in the transverse direction at a temperature of 150° C. using a biaxial stretching device to obtain a 30 μm thick stretched film (acrylic film). The optical properties of the stretched film were measured, and the results showed that the total light transmittance was 93%, the in-plane phase difference Δnd was 0.8 nm, and the thickness direction phase difference Rth was 1.5 nm.

[0216] Next, a polarizing film P1 was produced by the following method. First, a polyvinyl alcohol film with a thickness of 45 μm was dyed in a 0.3% iodine solution (temperature 30°C) between multiple rollers with different speed ratios for 1 minute, and stretched to a stretch ratio of 3 times. Next, the obtained stretched film was immersed in an aqueous solution (temperature 60°C) containing 4% boric acid and 10% potassium iodide for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, the stretched film was immersed in an aqueous solution (temperature 30°C) containing 1.5% potassium iodide for 10 seconds and washed. Next, a polarizer with a thickness of 18 μm was obtained by drying the stretched film at 50°C for 4 minutes. A TAC film with a thickness of 40 μm (manufactured by Konica Minolta, trade name "KC4UY") was bonded to one main surface of the obtained polarizer using a polyvinyl alcohol adhesive. The aforementioned acrylic film having a thickness of 30 μm was bonded to the other main surface of the polarizer with a polyvinyl alcohol-based adhesive. Thus, a polarizing film P1 was obtained.

[0217] (Example 1)

[0218] First, 50 parts of a solution containing PEDOT / PSS (Denatron PT-436 manufactured by Nagase ChemteX Corporation) and 50 parts of water were mixed to prepare a coating solution having a solid content concentration of 0.5% by weight. Next, the coating solution was applied to the surface of the acrylic film side of the polarizing film P1. The obtained coating film was dried at 80°C for 2 minutes to prepare a conductive layer. Thus, a polarizing film with a conductive layer was obtained. The thickness of the conductive layer was 30 nm.

[0219] Next, the adhesive layer C of the antireflection film AR1 was bonded to the surface of the TAC film of the polarizing film P1. The adhesive layer A was further transferred to the surface of the conductive layer to prepare a polarizing film with an antireflection film of Example 1 having a structure of antireflection film AR1 / polarizing film P1 / conductive layer / adhesive layer A.

[0220] (Example 2)

[0221] A polarizing film with an antireflection film of Example 2 was produced by the same method as in Example 1, except that the coating liquid of PEDOT / PSS was applied to the polarizing film P1 so that the thickness of the conductive layer would be 90 nm.

[0222] (Examples 3 to 12 and Comparative Examples 1 to 2)

[0223] Polarizing films with antireflection films of Examples 3 to 12 and Comparative Examples 1 to 2 were prepared by the same method as Example 1, except that the antireflection film, the conductive layer, and the adhesive layer were changed to the combinations shown in Table 2. It should be noted that in Comparative Example 2, the conductive layer was not formed on the polarizing film P1, and the adhesive layer A was directly bonded to the surface of the acrylic film side of the polarizing film P1.

[0224] (Example 13)

[0225] First, a coating solution having a solid content concentration of 0.27% by weight was prepared by mixing 9 parts of a solution containing PEDOT / PSS (Denatron P-580W manufactured by Nagase ChemteX Corporation) and 91 parts of water. Next, the coating solution was applied to the surface of the acrylic film side of the polarizing film P1. A conductive layer was prepared by drying the obtained coating film at 80°C for 2 minutes. Thus, a polarizing film with a conductive layer was obtained. The thickness of the conductive layer was 100 nm.

[0226] Next, the adhesive layer C of the antireflection film AR4 was bonded to the surface of the TAC film of the polarizing film P1. The adhesive layer A was further transferred to the surface of the conductive layer to prepare a polarizing film with an antireflection film of Example 13 having a structure of antireflection film AR4 / polarizing film P1 / conductive layer / adhesive layer A.

[0227] (Comparative Example 3)

[0228] First, 8.6 parts of a solution containing PEDOT / PSS (Denatron P-580W manufactured by Nagase ChemteX Corporation) and A coating liquid (solid content concentration of 0.5 wt %) for forming a conductive layer was prepared by mixing 1 part of a solution of an oxazoline acrylic polymer (trade name: EPOCROS WS-700, manufactured by Nippon Shokubai) and 90.4 parts of water. The concentration of the polythiophene polymer in the obtained coating liquid was 0.04 wt %, and the content of The concentration of the oxazoline acrylic polymer was 0.25% by weight.

[0229] Next, the obtained coating liquid was applied to the main surface of the polarizing film P1 on the acrylic film side. The obtained coating film was dried at 80° C. for 2 minutes to prepare a conductive layer. Thus, a polarizing film with a conductive layer was obtained. The thickness of the conductive layer was 60 nm.

[0230] Next, the adhesive layer C of the antireflection film AR10 was bonded to the surface of the TAC film of the polarizing film P1. The adhesive layer A was further transferred to the surface of the conductive layer to prepare a polarizing film with an antireflection film of Comparative Example 3 having a structure of antireflection film AR10 / polarizing film P1 / conductive layer / adhesive layer A.

[0231] <Optical properties of polarizing film with anti-reflection film>

[0232] In the polarizing films with antireflection films obtained in the examples and comparative examples, light from a CIE standard light source D65 was incident on the antireflection film in a state where the adhesive layer was laminated on the alkali-free glass in direct contact with the alkali-free glass. The light reflectances Y and L of the reflected light generated at this time were calculated by the above-mentioned method. * Value, a * Value and b * value, and satisfy L * Value = 0, a * Value = 0 and b * The color difference ΔE between the light with a value = 0 and the reflected light was evaluated. At this time, the polarizing film with an anti-reflection film was cut into 50 mm squares and used. As the alkali-free glass, EG-XG (thickness 0.7 mm) manufactured by Corning Incorporated was used. As the black film, a black film made of polyethylene terephthalate (PET) was used. The spectral reflectance was measured using a spectrophotometer (manufactured by Konica Minolta, Ltd., trade name "CM2600D"). The evaluation sample for evaluating the optical properties has a structure of a polarizing film with an anti-reflection film / alkali-free glass / black PET film. Among them, for the polarizing film with an anti-reflection film of Comparative Example 1, the reflected light was evaluated using an alkali-free glass on which an amorphous ITO layer (thickness 20 nm) was not formed on the surface. That is, in Comparative Example 1, the evaluation sample has a structure of a polarizing film with an anti-reflection film / ITO layer / alkali-free glass / black PET film. Sputtering was used to make the ITO layer. The Sn ratio of ITO contained in the ITO layer is 3 weight%. The Sn ratio was calculated from the weight of Sn atoms in ITO / (weight of Sn atoms+weight of In atoms).

[0233] <Optical properties of anti-reflection films>

[0234] For the antireflection films AR1 to AR10, the light reflectances Y1 and a1 of the reflected light generated when light from the CIE standard light source D65 is incident by the above method are * Value and b1 * The same black film, spectrophotometer, and the like as those used in the evaluation of the optical properties of the polarizing film with an antireflection film were used.

[0235] <Surface resistivity of adhesive layer>

[0236] The surface resistivity (Ω / □) of the adhesive layer A and B was measured at the stage of forming the adhesive layer A or B on the surface of the separator. The surface resistivity was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.). The measurement conditions were an applied voltage of 250 V and an applied time of 10 seconds.

[0237] <Surface resistivity of conductive layer>

[0238] In the examples and comparative examples, the surface resistivity (Ω / □) of the conductive layer was measured at the stage of forming the conductive layer on the surface of the polarizing film P1. In Example 13 and Comparative Example 3, the surface resistivity of the conductive layer was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and in accordance with the method specified in JIS K6911:1995. The measurement conditions were an applied voltage of 10 V and an application time of 10 seconds. In Examples 1 to 12 and Comparative Example 1, the surface resistivity of the conductive layer was measured using a resistivity meter (Loresta-GP MCP-T600 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and in accordance with the method specified in JIS K7194:1994. The measurement conditions were an applied voltage of 10 V and an application time of 10 seconds.

[0239] <Surface resistivity of polarizing film>

[0240] In Comparative Example 2, the surface resistivity of the polarizing film P1 was measured using a resistivity meter (Hiresta-UP MCP-HT450 manufactured by Mitsubishi Chemical Analytech Co., Ltd.) in accordance with the method specified in JIS K6911:1995. The measurement conditions were an applied voltage of 10 V and an applied time of 10 seconds. The surface resistivity of the polarizing film P1 was higher than 1.0×10 14 Ω / □.

[0241] <Loss of total light transmittance A caused by conductive layer>

[0242] First, the total light transmittance T1 of the polarizing film P1 was measured using a spectrophotometer (V7100 manufactured by JASCO Corporation) in accordance with the provisions of JIS K7361-1:1997. In the same way, the total light transmittance T2 of the laminate L composed of the polarizing film P1 and the conductive layer was measured at the stage where the conductive layer was formed on the surface of the polarizing film P1. The total light transmittance T2 of the laminate L was measured by allowing light to enter from the side of the polarizing film P1. The difference (T1-T2) between the total light transmittance T1 and the total light transmittance T2 of the polarizing film P1 was calculated, and the calculated value was regarded as the loss A of the total light transmittance caused by the conductive layer.

[0243] <ESD test>

[0244] First, the polarizing film with anti-reflection film obtained in the embodiment and the comparative example was attached to the surface of the visible side of the liquid crystal unit to produce a liquid crystal panel. Among them, for comparative example 1, a liquid crystal unit with an amorphous ITO layer (thickness 20nm) formed on the surface was used. That is, in comparative example 1, the liquid crystal panel has a structure of polarizing film with anti-reflection film / ITO layer / liquid crystal unit. The ITO layer was made by sputtering. The Sn ratio of ITO contained in the ITO layer is 3% by weight. Next, silver paste was applied with a width of 5mm in a manner covering the side of the polarizing film with anti-reflection film. The silver paste was dried to form a conductive structure composed of silver. The liquid crystal panel is electrically connected to the external ground electrode through the conductive structure. Next, the liquid crystal panel is mounted on the backlight device. Next, an electrostatic discharge (ESD) gun whose applied voltage is adjusted to 10kV is used to impart static electricity to the visible side (anti-reflection film side) of the liquid crystal panel. As a result, white spots are generated on a part of the liquid crystal panel. The time T from imparting static electricity until the white spot disappears is measured. In Table 2, the results of the ESD test were evaluated based on the following criteria related to the time T. In addition, the ESD test was performed under the conditions of 23° C. and 55% RH.

[0245] (Evaluation Criteria)

[0246] A: Less than 0.5 seconds

[0247] B: More than 0.5 seconds and less than 1 second

[0248] C: More than 1 second and less than 10 seconds

[0249] D: More than 10 seconds

[0250] <Color tone>

[0251] The liquid crystal panel produced in the above-mentioned ESD test was observed by naked eyes from the visible side (anti-reflection film side) to evaluate the color tone. In the color tone items in Table 2, A means no color tone was confirmed, B means very weak color tone was confirmed, C means weak color tone was confirmed, and D means color tone was confirmed.

[0252]

[0253] According to Table 2, the surface resistivity is 1.0×10 6 The polarizing films with anti-reflection films of Examples 1 to 13 with conductive layers of Ω / □ or less have good results in the ESD test compared with Comparative Examples 2 and 3, and it is inferred that the charging of the liquid crystal panel can be sufficiently suppressed. According to the results of the ESD test of Example 3 and Comparative Example 1, by using an adhesive layer to which a conductive material is added together with the conductive layer, the charging of the liquid crystal panel can be sufficiently suppressed compared with the case of using an ITO layer.

[0254] In addition, the liquid crystal panels with polarizing films with anti-reflection films of Examples 1 to 13, which have sufficiently low values ​​of the light reflectance Y of reflected light, fully suppress the reflection of light. It is inferred that these liquid crystal panels are suitable for improving the visual recognition of liquid crystal display devices. In contrast, in Comparative Example 1, due to the presence of the ITO layer, the light reflectance Y increases significantly, and the reflection of light in the liquid crystal panel cannot be fully suppressed.

[0255] Industrial Applicability

[0256] The liquid crystal panel of the present invention can be used for applications requiring good visibility, such as vehicle-mounted displays.

Claims

1. A liquid crystal panel comprising a polarizing film with an antireflection film and a liquid crystal cell, wherein the polarizing film with an antireflection film has an antireflection film, a polarizing film and an adhesive layer in this order in a lamination direction, and further has a conductive layer, No conductive layer is provided between the polarizing film with an anti-reflection film and the liquid crystal unit, The surface resistivity of the conductive layer of the polarizing film with an antireflection film is 5.0×10 5 Ω / □ or less, When the adhesive layer is stacked on the alkali-free glass in a manner that the adhesive layer is directly in contact with the alkali-free glass, the polarizing film with an anti-reflection film generates reflected light with a light reflectance Y of less than 1.1% when light from the CIE standard light source D65 is incident from the surface opposite to the adhesive layer.

2. The liquid crystal panel according to claim 1, wherein: The conductive layer included in the polarizing film with an antireflection film is disposed between the polarizing film and the pressure-sensitive adhesive layer.

3. The liquid crystal panel according to claim 1, wherein: The surface resistivity is 1.0×10 4 Ω / □ or less.

4. The liquid crystal panel according to claim 1, wherein: The surface resistivity is greater than 5.0×10 2 Ω / □.

5. The liquid crystal panel according to claim 1, wherein: The light reflectance Y is less than 0.9%.

6. The liquid crystal panel according to claim 1, wherein: The total light transmittance loss caused by the conductive layer of the polarizing film with an antireflection film is 0.9% or less.

7. The liquid crystal panel according to claim 1, wherein: The reflected light is L * a * b * a in the color system * Value and b * The values ​​satisfy the following relations (1) and (2), -10≤a * ≤10 (1) -18≤b * ≤5 (2)。 8. The liquid crystal panel according to claim 7, wherein: The a * The value is greater than -6 and less than 6.

9. The liquid crystal panel according to claim 8, wherein: The a * The value is greater than -3 and less than 3.

10. The liquid crystal panel according to claim 7, wherein: The b * The value is greater than -15 and less than 3.

11. The liquid crystal panel according to claim 10, wherein: The b * The value is greater than -10 and less than 2.

12. The liquid crystal panel according to claim 11, wherein: The b * The value is greater than -6 and less than 2.

13. The liquid crystal panel according to claim 1, wherein: The antireflection film includes a first high refractive index layer, a first low refractive index layer, a second high refractive index layer, and a second low refractive index layer in this order in a lamination direction.

14. The liquid crystal panel according to claim 13, wherein: The optical film thickness of the first high refractive index layer is 20 nm to 35 nm. The optical film thickness of the first low refractive index layer is 38 nm to 50 nm. The optical film thickness of the second high refractive index layer is 230nm to 290nm. The optical film thickness of the second low refractive index layer is 100 nm to 128 nm.

15. The liquid crystal panel according to claim 1, wherein: The adhesive layer includes a conductive material.